Sequence analysis of origins of replication in the Saccharomyces cerevisiae genomes - Li, Wen-Chao; Zhong, Zhe-Jin; Zhu, Pan-Pan; Deng, En-Ze; Ding, Hui; Chen, Wei; Lin, Hao (Frontiers in Microbiology, 2014)
DNA replication is a highly precise process that is initiated from origins of replication (ORI) and is regulated by a set of regulatory proteins. The mining of DNA sequence information will be not only beneficial for understanding the regulatory mechanism of replication initiation, but also for accurately identifying ORI. In this study, the GC profile and GC skew were calculated for the analysis of compositional bias in the Saccharomyces cerevisiae (S. cerevisiae) genome. We found that the GC content in the region of replication origins is significantly lower than that in the flanking regions. By calculating the information redundancy, an estimation of the correlation of nucleotides, we found that the intensity of adjoining correlation in replication origins is dramatically higher than that in flanking regions. Furthermore, the relation between ORIs and nucleosome as well as transcription start sites were investigated. Results show that ORIs are usually not occupied by nucleosomes. Finally, we calculated the distribution of ORIs in yeast chromosomes and found that most ORIs prefer to transcription terminal regions. We hope that these results will contribute to the identification of ORIs and to the mechanisms of DNA replication.